Extraction of Chlorophyll-a from Eutrophic Water by Repeated Freezing and Thawing-Extraction Method - Zeng, G.M.; Zhou, J.; Huang, T.; Liu, S.Y.; Ji, F.F.; Wang, P. (Asian Journal of Chemistry, 2014)
This work described the extraction processes of chlorophylls was analyze during two extraction techniques, namely the cool acetone method and acetone repeated freezing and thawing-extraction method as the chlorophyll-a extraction agent, and the results were compared. The objective of this study was to use the uniform design to optimization of the extraction of chlorophyll-a from freshwater green algae by two different methods used acetone. Extracted chlorophyll-a was investigated by fourier transform infrared spectroscopy. These results suggested that there is significant statistical difference between these two methods. The acetone repeated freezing and thawing-extraction method has more advantages than the rubbing-acetone method, which is faster and easier to handle, more complete extraction and lower toxic.